PERAN PENGAWAS PAI DALAM MENINGKATKAN KINERJA GURU PAI SD DI LOMBOK BARAT - Najwa, Lu`luin (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2023)
Abstract (English): This research was motivated by the lack of optimal supervision of West Lombok Elementary School PAI teachers. The purpose of this study is to describe PAI supervisors' role in improving PAI teachers' performance in elementary schools. The method used in this study is descriptive qualitative. The results showed that the role of PAI supervisors in improving teacher performance was carried out by 1) ensuring the implementation of the curriculum; 2) Supervise learning activities; 3) Provide guidance and supervision to teachers; 4) Monitor student progress; 5) Organizing training and workshops; 6) Coordinate with related parties; 7) Implement program evaluation and development; and 8) Maintain ethics and professionalism. Improving the performance of PAI teachers in elementary schools needs to pay attention to all aspects of supervision, supervision needs to be held on a scheduled basis by giving firmness to teachers to complete matters related to the implementation of learning.Key Words: Supervisor, teacher performanceÂ Abstrak (Indonesia):Penelitian ini dilatarbelakangi oleh belum optimalnya pengawasan terhadap guru PAI di SD Lombok Barat. Tujuan penelitian ini adalah untuk mendeskripsikan peran pengawas PAI dalam meningkatkan kinerja guru PAI di SD. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Hasil penelitian menunjukkan bahwa peran pengawas PAI dalam Meningkatkan kinerja guru dilakukan dengan 1) memastikan pelaksanaan Kurikulum; 2) Mengawasi kegiatan pembelajaran; 3) Memberikan bimbingan dan supervisi kepada guru; 4) Memonitor perkembangan siswa; 5) Menyelenggarakan pelatihan dan workshop; 6) Berkoordinasi dengan pihak terkait; 7) Menerapkan evaluasi dan pengembangan program; dan 8) Menjaga etika dan profesionalisme. Peningkatan kinerja guru PAI di SD perlu memperhatikan segala aspek pengawasan, supervisi perlu diadakan terjadwal dengan memberikan ketegasan pada guru untuk melengkapi hal-hal yang bersangkutan dengan pelaksanaan pembelajaran.Kata Kunci: Pengawas, Kinerja Guru